Accounting Principles. : With Working Papers. V.1 - Hermanson, Roger H., Ph.D. CPA.; Edwards, James Don, Ph.D. CPA.; Maher, Michael W., Ph.D. CPA. (USA : Irwin, 1992)
Accounting: the language of business, Processing accounting information, Assets and liabilities, Accounting, theory and partinerships, Corporation accounting.
Keywords: Accounting; Accounting -- Principles